Scientific Management and Religious Views - Mohiuddin, Md Golam (Journal of Islam and Science, 2021)
The main purpose of the study is to discuss Taylorism, known to us as scientific management, in the life code given to mankind by which was brought into existence in the life of prophet Muhammad (SAW) according to the Quran and Sunnah(Traditions of prophet), existing in an old, week, ignorant (Zahelia) social system, the main objectives of the management of prophet by investigating the worn out and inactive social system with utmost care and selection was to make the best utilization of human skill through establishing mutual good relation, eliminating conflicts and confusion by the best organizational strength of Islam.